A pattern-based approach for developing creativity applications supported by surface computing. Issue 110 (February 2018) - Magallanes, Yazmín; Sánchez, J. Alfredo; Cervantes, Ofelia; Wan, Wanggen
Highlights: An activity model for applications focused on creativity. Building blocks for constructing applications designed for creativity. By relying on our building blocks, applications were implemented in short time. Our building blocks prove the model's expressivity for describing creativity sessions. Abstract: Whereas creativity tasks have traditionally been supported by conventional media and tools (such as paper, pens, scissors and glue); mobile phones, tablets and other devices based on interactive surfaces are increasingly been used as additional support. Large-sized multi-touch interactive surfaces appear as an interesting alternative for supporting creativity processes and for supporting synchronous collocated collaboration. However, they have mostly been used for visualization and navigation purposes. Their use as authoring means, which would be essential in creativity tasks, has only begun to be explored. Applications and platforms that have been developed in this area rely on low-level primitives for implementing representation of ideas and discussions. We have identified a significant gap between the level of development tools and the abstractions required by end-user applications that aim to support creativity processes using interactive surfaces. This gap makes it difficult for developers to build applications that provide richer, more flexible support for innovators working collaboratively around interactive surfaces. Based upon a thorough analysis of existing applications and user practices in the field, we have identified the key actions and interaction patterns that take place during collaborative creativity sessions. Thus, we propose ISCALI (Innovation Solutions Centered on Activities for Large-sized Interfaces), a model that can be used both for describing and for prescribing the role of multi-touch surfaces in collaborative creativity tasks. In accordance to Activity Centered Design, ISCALI comprises three major components: activities, actions and operations. The central activities within the processes of creativity comprise generation, organization and evaluation of ideas. Each of these activities encompasses sets of actions. Finally, several operation sets achieve the goal of each of the actions. Based upon our model, we designed a general architecture for collaborative creativity applications. This architecture addresses the development gap through a proposed set of building blocks. These building blocks implement the main interaction patterns needed for stimulating creativity tasks that rely on interactive surfaces. We have implemented prototypical versions of these building blocks, referred to as TOKAs (Touch Operations for Creative Activities), and have made them available to developers. Independent developers have implemented applications that facilitate the use of various methodologies that foster creativity and synchronous collocated collaboration. These developers have taken advantage of the availability of TOKAs. The implementation and use of TOKAs demonstrate ISCALI's expressivity for describing and guiding the development of applications that support collaborative creativity on top of interactive surfaces.